Tratamento de efluente de laticínios em reator de leito estruturado submetido a diferentes condições operacionais - Aliberti, Edgar Augusto (2017)
The discharge of dairy effluents rich in organic and nitrogenous matter in water bodies can result in environmental impacts, therefore it is necessary to treat these wastewater. In this sense, the objective of this work was to evaluate the performance of a structured bed reactor and continuous flow, regarding the removal of organic matter and nitrogen, operated under continuous and intermittent aeration. The reactor used in the experiment had a useful volume of 2.125 L. As a support material, polyurethane foam with a diameter of 1.5 cm and a length of 48 cm was used and fixed by metal rods. The system was operated during the whole experiment with a hydraulic detention time of 16h and fed with effluent from the dairy industry, in which two phases of operation were studied: phase I being continuously aerated and phase II under intermittent aeration. In the continuous aeration phase the system was operated 24h with aeration, in the intermittent aeration phase a cycle was worked with 2 hours of aeration for 1 hour without aeration during 24h. Analyzes were made of pH, total alkalinity, temperature, Chemical Oxygen Demand (COD), Total Kjeldhl Nitrogen (NKT), N-ammoniacal-N-NH4 +, nitrite- N-NO2- and nitrate- N-NO3-. In Phase I there was a percentage of organic matter removal, NKT and NT of 93 ± 0.03 79 ± 16% and 61 ± 9%, respectively. In Phase II, 87 ± 0.03% of organic matter removal was obtained, 86 ± 10% of NKT and 76 ± 15% of NT removal. It was also verified that the efficiency of denitrification in the two phases was above 77%, being an indicative that the nitrification and simultaneous denitrification occurred. From the results it was concluded that in terms of removal of nitrogen and organic matter the system was efficient, but the operation in intermittent aeration conditions generates an economy to remove these pollutant loads since it reduces the aeration expense.